Stress analysis of overlapped crankshafts - Sime, Anthony P. (1998)
The crankshaft is a complex component, and as such, the influence of its geometric parameters on stresses seen under service loads is not well understood. The objectives of this work are to investigate the effects of a wide range of geometric parameters on stresses in overlapped crankshafts, to find correlation between results and to formulate simple methods of predicting peak stress levels: It is intended to achieve this by use of the Finite Element (FE) and Boundary Element (BE) methods.